EVALUATING EXXONMOBIL’S CONTRIBUTIONS TO PEACE AND SECURITY IN CHAD THROUGH THE PRISM OF LEGITIMACY THEORY - Shuriye, Mohamed (2010)
This study will explore the conflict-corporate nexus and the shifting discussion of expected norms of corporate behaviour in conflict zones. It will critically examine the perceived expectations of multi-national corporations’ engagement in conflict zones and strategies employed. Employing the critical prism of legitimacy theory and Feil et al’s framework on corporate contributions to peace and security in conflict zones, this study will explore the conflict-corporate dynamics using the case study of ExxonMobil’s operations in Chad to determine if there exist a ‘legitimacy gap’ between perceived corporate behavoiur and action. Determining if there is indeed a gap, this study will seek to answer what can explain its existence? More broadly this study will seek to contribute to existing CSR literature by highlighting the reporting approaches and challenges faced by corporations in conflict zones.